Potencial de reutilización de los residuos provenientes de tambos comerciales para la fertilización de recursos forrajeros - Burón Alfano, V. (2009)
Dairy production systems produce surpluses of nitrogen (N) and phosphorus (P) that are excreted in urine and feces, which increase the risk of contamination of soil and water. The objective of this study was to evaluate the potential of the reuse of nutrients present in excreta produced in dairy farms facilities as organic fertilizers by the calculation of (N) and (P) balances and to determine which feed component has a major influence in its variability. During 2006/2007, samples from all feed components of the milking cows (MC) were collected and analyzed in two grazing dairy farms (Castelli, Buenos Aires), with 241 (T1) and 91 (T2) MC, respectively. Nutrient balances were calculated by the difference between inputs (feeds) and outputs (milk) for each mineral. Daily permanence of MC was considered, in order to establish the balance excess that is transferred to the milking area. Nutrients deposited in dairy facilities by MC were between 1.47 to 2.61 kg N/MC/month and 0.22 to 0.45 kg P/MC/month and 5,420 kg N/year and 883 kg P/year (T1) and 2,126 kg N/year and 362 kg P/year (T2). Models estimated by simple linear regression showed that more than 79 % of the variability was explained by forage.\n